Tinjauan Klimatologis Kejadian Banjir Bandang di Kabupaten Lahat, Sumatera Selatan Tanggal 5 Juli 2023 - Mediany, Shinta; Haryanto, Yosafat Donni; Fadlan, Ahmad (Jurnal Fisika Unand, 2025)
BPBD reported that a flash flood occurred in Lahat Regency due to high rainfall in the early hours of Wednesday, July 5, 2023. This led to an overflow of the Lematang River, causing flooding that submerged roads and parts of residential areas. Therefore, research is essential to understand atmospheric dynamics and review climatological conditions during the flash flood event in Lahat Regency, covering Pulau Pinang District, Lahat District, and Mulak Sebingkai District. This research is expected to serve as a scientific basis for mitigation and adaptation measures against hydrometeorological disasters. Global phenomena such as the Madden–Julian Oscillation (MJO), El Niño Southern Oscillation (ENSO), and monsoon activity have been analyzed. The analysis of local and regional-scale meteorological parameters was conducted using atmospheric reanalysis datasets from JRA-3Q, NCEP/NCAR, and NCICS. Additionally, a climatological review was carried out based on rainfall data from several cooperative rain gauge stations around the affected area, supplemented with GSMaP satellite data. The study indicates that the flash flood was caused by heavy to very heavy rainfall in the surrounding areas. This rainfall resulted from several factors, including the active MJO over the Indian Ocean, wind convergence, and the presence of the Intertropical Convergence Zone (ITCZ) extending along the western part of Sumatra. The presence of a low-pressure area enhanced the potential for convective cloud formation, further intensified by atmospheric moisture levels exceeding 80% at the 850 mb layer, increasing water vapor content in the upper atmosphere. A historical data review shows that, climatologically, the rainfall during the flash flood event represented the highest recorded daily maximum rainfall for July within the observation period, surpassing pentad and decadal averages. The influence of global, regional, and local-scale phenomena contributed to the increased rainfall intensity in the flash flood-affected area.